Microwave-assisted solvothermal synthesis and electrochemical characterizations of ternary perovskite NiTiO3 anode materials for lithium-ion batteries. Issue 15 (15th October 2019) - Lu, Chung-Hsin; Naresh, N.; Kumar, P. Senthil; Som, Sudipta
Abstract: Perovskite-structured NiTiO3 powders were synthesized via the microwave-assisted solvothermal and conventional solvothermal processes for the application of anode materials in Li-ion batteries. In the conventional solvothermal process, a pure perovskite phase was not achieved, and a TiO2 impurity phase existed. Whereas, pure perovskite NiTiO3 powder with a rhombohedral structure was successfully synthesized using the microwave-assisted solvothermal process. The developed microwave-assisted process considerably reduced the total required heating time for preparing the pure perovskite phase. In both processes, the obtained powders displayed micro-rod shaped morphology. Electrochemical analysis showed high specific discharge capacity (750 mAh/g) at a current density of 0.1C and promising capacity retention (177 mAh/g) after the 90th cycle, with a coulombic efficiency of 90%. By comparison, the sample synthesized through the conventional approach delivered a lower specific discharge capacity of 737 mAh/g at a current density of 0.1C. Electrochemical impedance spectroscopy analysis indicated that the charge-transfer resistance R ct values of NiTiO3 powder synthesized using the microwave-assisted and conventional approaches were 16 and 23 Ω, respectively. The improved electrochemical performances and lower R ct values could be ascribed to the improved crystallinity and surface morphology of NiTiO3 powders derived from the microwave process. The present research indicated that the microwave-assisted solvothermal synthesis is a potential approach to synthesize NiTiO3 anode materials for high-performance lithium-ion batteries.